2013
DOI: 10.1007/s10552-013-0165-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary consumption and diet diversity and risk of developing bladder cancer: results from the South and East China case–control study

Abstract: Our results indicate that a diet with higher total diet diversity and in particular fruit diversity may reduce the risk of bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…The study by Sacerdote et al (2007) provided two categories of exposure and was thus not included. The other 11 studies were excluded because of lack of data on person-time (Shibata et al, 1992;George et al, 2009;Grant et al, 2012), the dose (g/day) of each category (Riboli et al, 1991;La Vecchia et al, 1999;Wakai et al, 2004;Wu et al, 2012;Isa et al, 2013;Park et al, 2013) and noncases or total cases of each category (Wakai et al, 2000;Aune et al, 2009). We found a decreased bladder cancer risk of 8% for every 200 g/day increment in vegetable consumption (RR = 0.92; 95% CI: 0.87-0.97; Fig.…”
Section: Dose-response Analysismentioning
confidence: 77%
See 2 more Smart Citations
“…The study by Sacerdote et al (2007) provided two categories of exposure and was thus not included. The other 11 studies were excluded because of lack of data on person-time (Shibata et al, 1992;George et al, 2009;Grant et al, 2012), the dose (g/day) of each category (Riboli et al, 1991;La Vecchia et al, 1999;Wakai et al, 2004;Wu et al, 2012;Isa et al, 2013;Park et al, 2013) and noncases or total cases of each category (Wakai et al, 2000;Aune et al, 2009). We found a decreased bladder cancer risk of 8% for every 200 g/day increment in vegetable consumption (RR = 0.92; 95% CI: 0.87-0.97; Fig.…”
Section: Dose-response Analysismentioning
confidence: 77%
“…The remaining 57 were considered to be of potential value and the full text was reviewed for detailed evaluation. Finally, 12 cohort studies (Shibata et al, 1992;Chyou et al, 1993;Michaud et al, 1999Michaud et al, , 2002Zeegers et al, 2001;Holick et al, 2005;Sakauchi et al, 2005;Larsson et al, 2008;George et al, 2009;Grant et al, 2012;Ros et al, 2012;Park et al, 2013) and 15 case-control studies (Riboli et al, 1991;Bruemmer et al, 1996;Yu et al, 1997;La Vecchia et al, 1999;Pohlabeln et al, 1999;Wakai et al, 2000;Pelucchi et al, 2002;Wakai et al, 2004;Kellen et al, 2006;García-Closas et al, 2007;Tang et al, 2008;Aune et al, 2009;Lin et al, 2009;Wu et al, 2012;Isa et al, 2013) involving 12 417 cases and 1 766 557 participants were Table 1). The characteristics of the included cohort studies and case-control studies are summarized in Supplementary Tables 2 and 3, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, Kim et al (33) reported significant inverse association between milk and milk products and gastric cancer risk with case-control study design, whereas Chun et al (32) reported a positive association between milk intake and colorectal cancer risk with similar study design. In China, a case-control study on bladder cancer (34) reported strong health benefits of dairy foods, and another case-control study demonstrated potential protective effects of milk intake on breast cancer (41) . In Japan, a case-control study (42) found statistically significant inverse association between calcium and vitamin C intake and colorectal cancer, and potential inverse association between milk and other dairy food intake, and colorectal cancer risk.…”
Section: Association Of Meat and Milk Consumption With Cancer And Metmentioning
confidence: 99%
“…Of the 14 articles, two were population-based case-control studies (Castelao et al, 2004;Kellen et al, 2006), six were hospital-based case-control studies (Balbi et al, 2001;De Stefani et al, 2008;García-Closas et al, 2007;Isa et al, 2013;Lin et al, 2009;Sacerdote et al, 2007), and six were cohort studies (Buchner et al, 2009;Holick et al, 2005;Larsson et al, 2008;Li et al, 2010;Michaud et al, 1999;Park et al, 2013). Seven studies had been conducted in North or South America (Balbi et al, 2001;Castelao et al, 2004;De Stefani et al, 2008;Holick et al, 2005;Lin et al, 2009;Michaud et al, 1999;Park et al, 2013), five in Europe (Buchner et al, 2009;García-Closas et al, 2007;Kellen et al, 2006;Larsson et al, 2008;Sacerdote et al, 2007), and two in Asia (Isa et al, 2013;Li et al, 2010). Five studies assessed citrus fruit consumption by mailed questionnaire (Holick et al, 2005;Larsson et al, 2008;Li et al, 2010;Michaud et al, 1999;Park et al, 2013); the remainder were assessed by interview (Balbi et al, 2001;Buchner et al, 2009;Castelao et al, 2004;De Stefani et al, 2008;García-Closas et al, 2007;<...>…”
Section: Literature Searchmentioning
confidence: 99%